“The Production of Post-Supernaturalistic Mythopoesis in Contemporary Nature Religion” - LeVasseur, Todd (Worldviews, 2012)
Are there new, emerging forms of nature reverencing religion? If so, what might these look like? This paper seeks to answer this question by drawing on both Bron Taylor's Dark Green Religion (and especially his nature religion schema found therein that includes the category of “Gaian Earth Religion”) and the work of environmental philosopher Donald Crosby (and his category of “religion of nature”). I argue that science writers like Edward Wilson and Carl Sagan, along with ecopoets like Mary Oliver, are creating a new mythopoesis of post-supernaturalistic nature religion. I also look at the complex interaction of religion/science and the role reverence for nature plays in this dialogue. I argue that the nature religion schema put forth by Taylor and the “physisology” put forth by Crosby can help us better theorize emerging strands of post-supernaturalistic religious-like sentiments and narratives that continue to grow 150 years after Darwin's theory revolutionized both science and religion.